A cyclic slip irreversibility based model for fatigue crack initiation of nickel base alloys. (September 2017) - Ho, H.S.; Risbet, M.; Feaugas, X.
Highlights: A microstructure-based reformulation of the modified MC law is discussed for Waspaloy. The law is formulated using cyclic slip irreversibility parameter obtained by AFM. The modified MC law is valid for damage initiation in polycrystal Waspaloy. Our approach allows giving a physical base of engineering law. Abstract: The opportunity to define a microscopic law of fatigue crack initiation using Manson-Coffin law formulated in terms of cyclic slip irreversibility deduced from AFM measurements is discussed for a polycrystalline superalloy with different grain sizes and precipitate sizes. The results show that the modified Manson-Coffin law, relating cyclic slip irreversibility parameter to fatigue crack initiation life, is sustained through a two-parameter power law: ε f ′ and c . The analysis suggests that the exponent c -value can be related to the degree of plastic strain incompatibility between grains, and the cumulative irreversible cyclic plastic strain to crack initiation is a relevant damage indicator for crack initiation. Consequently, our approach allows giving a physical base of engineering law.